2011
DOI: 10.1002/eji.201041216
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diabetogenic action of CD4+ T lymphocytes requires Fas expression and is independent of IL‐1 and IL‐18

Abstract: CD4+ T lymphocytes are required to induce spontaneous autoimmune diabetes in the NOD (Non Obese Diabetic) mouse. Since pancreatic β cells upregulate Fas expression upon exposure to pro-inflammatory cytokines, we studied whether the diabetogenic action of CD4+ T lymphocytes depends on Fas expression on target cells. We assayed the diabetogenic capacity of NOD spleen CD4+ T lymphocytes when adoptively transferred into a NOD mouse model combining: a) Fas-deficiency, b) FasL-deficiency, and c) the SCID mutation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
(64 reference statements)
2
11
0
Order By: Relevance
“…In addition to IL-1β, NLRP3 also activates IL-18. The role of IL-18 in T1D is controversial; some studies suggest that IL-18 promotes T1D development (37), possibly through inducing diabetogenic T-cell expansion in NOD mice (38), whereas other studies, including our own, indicate that IL-18 is not required for T1D development (18,19). However, the role of IL-18 in diabetes protection in the NLRP3-deficient NOD mice is not clear.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition to IL-1β, NLRP3 also activates IL-18. The role of IL-18 in T1D is controversial; some studies suggest that IL-18 promotes T1D development (37), possibly through inducing diabetogenic T-cell expansion in NOD mice (38), whereas other studies, including our own, indicate that IL-18 is not required for T1D development (18,19). However, the role of IL-18 in diabetes protection in the NLRP3-deficient NOD mice is not clear.…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, the role of the inflammasome pathway in the pathogenesis of T1D is unclear. Although caspase-1 or IL-1β deficiency did not protect NOD mice from T1D (18,19), IL-1 blockade showed a synergistic protective effect when combined with anti-CD3 therapy for T1D in a mouse model (20). Interestingly, recent genetic association studies suggested that polymorphisms in inflammasome genes might be involved in the predisposition to T1D.…”
mentioning
confidence: 99%
“…Induced Fas transcription and modulation of expression is caused by a number of proinflammatory cytokines including IL-1α, IL-1β, IFNγ, nitric oxide (NO), and TNF-α that synergize with Fas as effector mechanisms of β-cell destruction (37, 41). Furthermore, both Fas expression induced by IL-1β (42) independent of NFκB activation (43, 44) and islet sensitization to apoptosis (45, 46) also evolve as direct consequences of hyperglycemia. The vast changes in transcriptomes and expression profiles of the inflamed islets may be viewed as an effort of the tissue to sustain insulin production and increase β-cell mass.…”
Section: The Fas/fasl Interaction In Inflammatory Insulitismentioning
confidence: 99%
“…[5][6][7] The inefficiency of the hybridoma and phage methods provided us with an opportunity to change the way we make monoclonal antibodies. The Antibody Discovery Group at UCB developed a B cell culture method, 8,9 linked to homogeneous assays and a sensitive PCR process to clone out the cognate antibody V region genes. 10 This methodology has given us a greater ability to screen the antibody repertoire of an immunized animal, allowing the screening of more than a billion B cells in a campaign over 2 weeks, to select a panel of antibodies, that after further in vitro and in vivo secondary screening, have the potential to be therapeutic antibody candidates.…”
Section: Introductionmentioning
confidence: 99%